Gender differences and risk factors for acute kidney injury following cardiac surgery: A single center retrospective cohort study - Yichuan Wang; Xuliang Huang; Shanshan Xia; Qingqing Huang; Jue Wang; Maochao Ding; Yunchang Mo; Jianping Yang (Heliyon, 2023)
Background: We studied AKI incidence and prognosis in cardiac surgery patients under and over 60 years old. Methods: We studied AKI in patients who underwent cardiac surgery at the First Affiliated Hospital of Wenzhou Medical University between Jan 2020 and Dec 2021, using improved global prognostic criteria for diagnosis. Results: After analyzing 781 patients (402 males, 379 females), AKI incidence after surgery was 30.22 %. Adjusting for propensity scores revealed no significant difference in AKI incidence between young males (24.1 %) and females (19.3 %). However, young females had higher AKI stages. Among older patients, AKI incidence was comparable between males (43.4 %) and females (42.2 %), but females had longer intubation times. Independent risk factors for AKI included age, male gender, and BMI, while intraoperative hemoglobin level was protective. Conclusions: No gender gap in AKI frequency for <60 years old and ≥60 years old post-cardiac surgery, yet women display increased AKI severity and extended intubation duration.